2012
DOI: 10.1182/blood.v120.21.3100.3100
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Outcome of Related Allogeneic Hematopoietic Cell Transplantation in Patients with Fanconi Anemia.

Abstract: 3100 Background: Hematopoietic cell transplantation (HCT) can cure bone marrow failure in patients with Fanconi Anemia (FA), and it is generally accepted that these patients should receive low intensity conditioning due to the underlying DNA repair defect in their cells. Outcomes of recipients of matched related HCT have generally been favorable, but only few studies have scrutinized the factors that may impact on the eventual outcome of these patients. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
2
14
1
1
Order By: Relevance
“…resulting in a marked reduction in the doses of agents used in HCT preparatory regimens [1][2][3][8][9][10][11]. The use of low-dose cyclophosphamide and, more recently, the introduction of fludarabine have radically improved HCT outcomes in patients with FA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…resulting in a marked reduction in the doses of agents used in HCT preparatory regimens [1][2][3][8][9][10][11]. The use of low-dose cyclophosphamide and, more recently, the introduction of fludarabine have radically improved HCT outcomes in patients with FA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, FA is characterized by congenital malformations, progressive marrow failure, and a predisposition to acute myelogenous leukemia and solid tumors [4][5][6][7]. Hematopoietic stem cell transplantation (HCT) remains the sole modality with the potential to restore normal hematopoiesis in these patients [8][9][10][11]. Although HCT from an HLA-matched related donor has been categorically associated with excellent outcomes in many patients, a higher incidence of treatment failure has been reported in recipients of unrelated donor HCT [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was limited by the small sample size; however, we showed that FANCJ FA patients with a matched related donor could be conditioned using low dose cyclophosphamide similar to previous reports. 12,13 We also showed that unrelated transplant in FANCJ FA can be successfully performed using non-radiation based conditioning. The use of alemtuzumab-based conditioning regimen coupled with high dose CD34 and depletion of TCR-alpha/beta and CD19 should be further studied in larger sample size in FA patients undergoing transplant from matched unrelated donor transplant.…”
mentioning
confidence: 79%
“…Следует отметить, что у 82,1% пациентов с ГЦ был использован ЦФ либо в режиме кон диционирования, либо и/или после аллоТГСК на +3/+4 дни, однако при многофакторном анализе влияние ЦФ не подтвердилось. В ряде статей, посвященных ГЦ, ав торы указывают на наличие взаимосвязи между разви тием ГЦ и наличием ЦФ в режимах кондиционирования, используемого в большей степени при МАК [7,53].…”
Section: материалы и методыunclassified